Development of the First Patient‐Reported Experience Measure (PREM) for Hearing Loss in Audiology Care—My Hearing PREM - Sian K. Smith; Georgina Burns O'Connell; Rebecca Knibb; Rosemary Greenwood; Saira Hussain; Rachel Shaw; Jean Straus; Jonathan Banks; Amanda Hall; Nisha Dhanda; Sian Noble; Helen Pryce (Health Expectations, 2024)
ABSTRACT Context Patient‐reported experience measures (PREMs) provide important insights into the challenges experienced when living with a chronic condition. Although patient‐reported outcome measures (PROMs) exist in audiology, there are no validated PREMs to help clinicians understand patient perspectives and identify areas where patients may need additional support or interventions. Objective The aim of this study was to develop and evaluate content for the new ‘My Hearing PREM’, which captures lived experiences of hearing loss from patients’ perspectives. Design My Hearing PREM was developed and tested in two key phases. Phase 1 involved generating the PREM prototype in accordance with our conceptual model of the lived experience of hearing loss. In Phase 2, cognitive interviews were conducted with adults with hearing loss to appraise the content of the PREM (relevance, clarity, acceptability and comprehensiveness) and assess its respondent burden. Key stakeholders (e.g., adults with hearing loss, patient and public representatives, clinicians and researchers) were consulted throughout Phases 1 and 2 to review and refine the PREM. Interview data were analysed using thematic analysis. Setting and Participants Sixteen participants (aged 16 years and over) with hearing loss took part in cognitive interviews, recruited from UK audiology departments and non‐clinical settings (e.g., lip‐reading classes, national charity links and social media). Results Most PREM items were found to be relevant, clear, acceptable and comprehensive. Several problems were identified, including items not working well with the response scale options, irrelevant questions and a lack of clarity about terms (e.g., healthcare professionals) and whether questions should be answered based on the use of hearing aids (or not). The PREM was amended accordingly. Conclusions Currently, no hearing loss‐specific PREMs exist in audiology. Involving multiple stakeholders in the development of the PREM helped to ensure that the items were relevant, clear, acceptable and comprehensive. The PREM is undergoing further evaluation and refinement in preparation for investigating the feasibility of implementing it into clinical practice. Patient or Public Contribution Ongoing Patient and Public Involvement and Engagement (PPIE) with key groups (South Asian Women's groups, young people's groups, learning disability networks and student populations) was integral to the study. PPIE members reviewed patient information sheets and consent forms, advised on recruitment, reviewed the interview schedule and checked coding and analysis procedures. PPIE members provided feedback on the PREM's comprehensibility. Members of the public, including adults attending lip‐reading classes and hearing aid users from the South Asian community, provided feedback on iterative PREM drafts.